Media Frame Covid-19 News on Economic Aspect of Vaccination in Timor-Leste: - - Gonçalves, Miguel; Sunarto Ngadiyono , Sunarto (Jurnal Komunikasi, 2023)
To deal with the pandemic situation, the challenge of prevention, the media covers the issue of vaccination, sometimes covering both sides and also on the newspaper side. Prevention of COVID-19 is a complex and common problem, due to the economy and people who are able to provide them and tools such as hand sanitizers, masks and vaccinations. People trying to access public services, business and applying to work and other activities need to show proof of vaccines. This study aims to know the framing of the Covid-19 news in the economic aspect of vaccination in Timor-Leste. The media describe issues that are considered important and shape public opinion and agenda, leading people with certain agendas to be raised by the media and may be considered quite interesting and actual. The method used is a qualitative method with the Entman model framing analysis with fourth procedure: (1) Defining the problem; (2) diagnose causes; (3) make moral judgments; and (4) treatment recommendations. Data collected from the Independent Post with 6 news headlines April-May 2021. The results show that the media frames information about Covid-19 related to the global economy through business promotion in pharmaceuticals for supplying countries vaccines and the national economy that focus more on the strategies and policies issued by the central and local governments in response to the implementation of vaccinations to link challenges and citizen participation as the only criteria for remaining free to move for economic recovery activities. The information’s about the Covid-19 vaccines from various perspectives. The consequence of this practice is that no new information is available to the public, so the public space is only filled with news that is in line with the economic aspects of vaccination in Timor-Leste.